Removal of organic using solar-fenton technology [compact disc] - 364399 Darina Kaur Parjan Singh (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006